Multigene phylogeny, phylogenetic network, and morphological characterizations reveal four new arthropod-associated Simplicillium species and their evolutional relationship - Chen, Wanhao; Liang, Jiandong; Ren, Xiuxiu; Zhao, Jiehong; Han, Yanfeng; Liang, Zongqi (Frontiers in Microbiology, 2022)
Simplicillium species are widely distributed and commonly found on various substrates. A minority of species are associated with arthropods. A spider-associated species Simplicillium araneae, and three insect-associated species, S. coleopterorum, S. guizhouense, and S. larvatum, are proposed as novel species based on a multi-locus phylogenetic analysis and morphological characteristics. These Simplicillium species completely fit the nutritional model of Hypocreales fungi, and could be used as a model to study their evolutionary relationship. A phylogenetic network analysis based on ITS sequences suggests that a host jump was common among Simplicillium species, and S. araneae may have originally come from an insect host and then jumped to a spider host. However, the evolutionary relationship of S. coleopterorum, S. guizhouense, and S. larvatum was not clear in the phylogenetic network and more sequencing information should be added to the network. In addition, strain CBS 101267 was identified as S. subtropicum.